Highly sensitive and selective ion-imprinted polymers based on one-step electrodeposition of chitosan-graphene nanocomposites for the determination of Cr(VI). (1st September 2018) - Wu, Shuping; Dai, Xiangzi; Cheng, Tingting; Li, Songjun
Graphical abstract: Highlights: A novel ion-imprinted sensor (IIP-S) has been developed for Cr(VI) detection. IIP-S was successfully synthesized via one-step electrodeposition. IIP-S exhibited high selectivity for Cr(VI) detecting in the presence of other ions. IIP-S provided excellent stability and good repeatability. IIP-S was successfully applied to detecting Cr(VI) in real samples. Abstract: A sensitive and selective electrochemical sensor based on ion-imprinted chitosan-graphene nanocomposites (IIP-S) has been developed for the determination of Cr(VI). The ion-imprinted polymers were constructed by one-step electrodeposition. The morphology and structure of IIP-S were characterized by SEM, TEM, XRD, FTIR and EDS, respectively. Meanwhile, the electrochemical behavior of IIP-S was investigated using CV, EIS and DPV. The linear range of IIP-S was from 1.0 × 10 −9 to 1.0 × 10 −5  mol/L, with the low detection limit of 6.4 × 10 −10  mol/L (S/N = 3). The sensor exhibited high selectivity for the determination of Cr(VI) in the presence of Zn(II), Co(II), Cu(II), Ni(II), Mn(II), MnO 4−, C2 O4 2−, S2 O6 2− and MoO4 2− ions. The IIP-S also provided excellent stability and good repeatability that the sensitivity remained 85% after 9 cycles of rebinding-removal, while the sensitivity retained 87% of its initial response storing at 4 °C for 17 days. Moreover, it was successfully applied to the detection of Cr(VI) ions in tap water and river water.